The effect of the Cort 1 program to expand the perception of some basic motor skills for children aged (4-5) years - Nadeem Ahmed, Maysa; Namoos AL-Taie, Dhafer (International Journal of Psychosocial Rehabilitation, 2020)
To reveal the effect of the Kurt program (1) to expand the perception of some basic motor skills in children aged (4-5) years, the researchers used the experimental approach on a sample of (40) children, distributed into two groups, after implementing the program, conducting specialized tests, obtaining data and processing them statistically. The two researchers reached the most important conclusions, including: The program worked to improve and expand the awareness of the experimental research sample in the performance of some basic motor skills. The researchers recommend the necessity of adopting the Kurt (1) program in teaching and improving the motor skills of kindergarten children in Diyala governorate through the establishment of training courses for teacher’s Physical education in kindergartens in the governorate. And conducting other studies dealing with the Kurt program with its other parts in structural, motor and mental variables for other age groups.